2019
DOI: 10.24123/aipj.v33i4.1798
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Subjective Wellbeing, and Work-Family Conflict Among University Lecturers

Abstract: The purpose of this study is to determine the role of emotional intelligence and subjective wellbeing in predicting work-family conflict. The participants for the study were 182 female lecturers at University of Sriwijaya, and the pilot study of the measuring scales was conducted with 52 lecturers. The scales used were the scales of emotional intelligence, subjective well-being and work-family conflict. Data analysis employed multiple linear regression. The results of the analysis were that there is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Findings of the studies have revealed that emotional intelligence enhances individual emotional and intellectual capacity, lets him accurately identify the behaviors, and acts accordingly [37,63,89]. Similarly, studies related to WFC also highlighted EI as a factor that is strongly associated with WFC [69,81].…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Findings of the studies have revealed that emotional intelligence enhances individual emotional and intellectual capacity, lets him accurately identify the behaviors, and acts accordingly [37,63,89]. Similarly, studies related to WFC also highlighted EI as a factor that is strongly associated with WFC [69,81].…”
Section: Emotional Intelligencementioning
confidence: 99%